Changes in nasal structures following orthopaedic and a surgically assisted rapid maxillary expansion - KURT, GÖKMEN; Altug-Atac, A. T.; Atac, M. S.; Kurt, GÖKMEN; Karasud, H. A. (My University, 2010)
The aim of this study was to investigate and compare changes ill the nasomaxillary complex substructures following orthopaedic rapid maxillary expansion (RME) and Surgically assisted RME (SARME). 10 patients received RME, 10 patients received SARME, and 10 patients served as all untreated control group. Lateral and posteroanterior cephalograms were obtained for each individual at pre-expansion/pre-control (T1) and post-expansion/post-control (T2). Descriptive parameters and transversal measurements on maxillo-mandibular dentoalveolar structures and skeletal bases, right and left nasal cavity angles (NC/Lom/VL and CN/Lom/VL, respectively), total nasal cavity angle (NC/Lom/CN), nasal cavity width (NC-CN) and nasal septum angle (sn/Lom/VL) were also calculated. Paired t-tests were used to evaluate changes within groups following treatment/control. Analysis of variance (ANOVA) and Duncan-s tests were used to compare changes between groups. With the exception of nasal septum deviation, all nasal parameters significantly increased following RME and SARME. The increases in the SARME group were greater than in the other groups, but no statistically significant differences were recorded between the RME and SARME groups. Neither RME nor SARME created positional changes in the nasal septum.